Decomposition of additive-free formic acid using a pd/c catalyst in flow: Experimental and cfd modelling studies - Hafeez, Sanaa; Sanchez, Felipe; Al-Salem, S. M.; Villa, Alberto; Manos, George; Dimitratos, Nikolaos; Constantinou, Achilleas (My University, 2021)
The use of hydrogen as a renewable fuel has gained increasing attention in recent years due to its abundance and efficiency. The decomposition of formic acid for hydrogen production under mild conditions of 30◦ C has been investigated using a 5 wt.% Pd/C catalyst and a fixed bed microreactor. Furthermore, a comprehensive heterogeneous computational fluid dynamic (CFD) model has been developed to validate the experimental data. The results showed a very good agreement between the CFD studies and experimental work. Catalyst reusability studies have shown that after 10 reactivation processes, the activity of the catalyst can be restored to offer the same level of activity as the fresh sample of the catalyst. The CFD model was able to simulate the catalyst deactivation based on the production of the poisoning species CO, and a sound validation was obtained with the experimental data. Further studies demonstrated that the conversion of formic acid enhances with increasing temperature and decreasing liquid flow rate. Moreover, the CFD model established that the reaction system was devoid of any internal and external mass transfer limitations. The model developed can be used to successfully predict the decomposition of formic acid in microreactors for potential fuel cell applications.
Keywords: Computational fluid dynamics (CFD); Formic acid decomposition; Green chemistry; H2 production; Mi-croreactors; Pd catalyst